Detection of Malaysian methicillin-resistant Staphylococcus aureus (MRSA) clinical isolates using simplex and duplex real-time PCR - Suhaili, Zarizal; Ali, Abd Manaf; -, Johari; -, S.A.b (2009)
The aim of this study was to develop a methicillin-resistant Staphylococcus aureus (MRSA) detection method based on the melting temperature analysis profiling of S. aureus clinical isolates from three different hospitals in Malaysia. Simplex and duplex real-time PCR assay was used for the simultaneous detection of nuc (species-specific) and mecA (methicillin-resistance) genes in a single SYBR Green Ireal-time PCR tube assay. Evaluations were based on the melting temperature (T m) analysis of the amplicons using 23 S. aureus clinical isolates including three ATCC S. aureus standard strains. Real-time PCR amplification products with melting peaks at 78.39 ± 0.4°C and 74.41 ± O .G C were detected for nuc and mecA genes, respectively. Each real-time PCR assay was completed within two hours. This rapid genotypic method is useful for the detection of resistant determinant (mecA) and identification of S. aureus (nuc) clinical isolates, thus benefiting patient therapy in hospitals.© 2008 Springer Science+Business Media 8.V.